A new robust-possibilistic reliable hub protection model with elastic demands and backup hubs under risk. (November 2019) - Rahimi, Yaser; Torabi, S. Ali; Tavakkoli-Moghaddam, Reza
Abstract: This research considers a new reliable backup hub under the robust-possibilistic uncertainty. The considered multi-objective model aims to minimize the total transportation cost of a p -hub median protection model while maximizing the flow between each pair node and minimizing the total transportation time. Additionally, it considers the potential disruption risks in the hub links of the transportation network for which a failure mode and effect analysis (FMEA) method is used to measure the risk of network's arcs. Consequently, the demand is assumed to be dependent on the utility proposed by each hub. Thus, the demand elasticity is considered in this paper. As the exact values of some parameters are not known in advance, a fuzzy multi-objective decision making-based approach is proposed to optimally solve small-sized problems. Furthermore, a number of sensitivity analyses are done on a real case study in the Iranian Road Transportation Sector with useful managerial insights. Graphical abstract: Highlights: Designing a new reliable p -hub protection model with elastic demand. Using financing tools for establishing hubs. Measuring the risk level of arcs in the hub network. Devising a two-phase solution method. Considering a real-case study in the Road Transportation sector of Iran.